2016
DOI: 10.1117/1.nph.3.3.031413
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of auxiliary diagnosis index for autism spectrum disorder using near-infrared spectroscopy

Abstract: Abstract. Lack of a diagnostic index is a problem that needs to be overcome in the diagnosis of autism spectrum disorder (ASD), because this problem prevents an objective assessment based on biomarkers. This paper describes the development of a diagnostic index for ASD using near-infrared spectroscopy (NIRS). We investigated continuous prefrontal hemodynamic changes depending on reciprocal disposition of working memory and nonworking memory tasks using two-channel NIRS. NIRS signals in the prefrontal cortex we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Nine fNIRS studies have investigated working memory and inhibition in ASD. These studies observed an atypical activation in the PFC during letter-fluency tasks (Iwanami et al, 2011(Iwanami et al, , 2010Kawakubo et al, 2009), working memory tasks (Narita, 2015;Yanagisawa et al, 2016) and task switching/inhibition (Funabiki et al, 2012a(Funabiki et al, , 2012bNarita et al, 2012).…”
Section: Working Memory and Inhibitionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nine fNIRS studies have investigated working memory and inhibition in ASD. These studies observed an atypical activation in the PFC during letter-fluency tasks (Iwanami et al, 2011(Iwanami et al, , 2010Kawakubo et al, 2009), working memory tasks (Narita, 2015;Yanagisawa et al, 2016) and task switching/inhibition (Funabiki et al, 2012a(Funabiki et al, , 2012bNarita et al, 2012).…”
Section: Working Memory and Inhibitionmentioning
confidence: 98%
“…Studies of working memory conversion showed that a switching tendency of hemodynamic activation in the PFC was obvious in TDC but was not shown instantly in ASD (Narita et al, 2012;Yanagisawa et al, 2016). Regarding inhibitory control ability in ASD, studies showed reduced activation in the right PFC during a Go/No-go task (Funabiki et al, 2012;Xiao et al, 2012) compared to a TDC group and in the left ventrolateral PFC during a stop signal task compared to an ADHD group (Ishii-Takahashi et al, 2014).…”
Section: Working Memory and Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color and shape span task A weighted separability index based on the HbO levels was utilized to reveal signi¯cant di®erences between the left dorsolateral PFCs of ASD patients and healthy persons during a working memory task. 45…”
Section: Stop-signalmentioning
confidence: 99%
“…Several fNIRS studies on ASD have shown that children with ASD experience atypical cortical activity in cognitive tasks [16][17][18][19] as well as in resting-state [20,21]. For examples, when watching a cartoon, weak network efficiency and deficits in information exchange were observed in children with ASD [16,17].…”
Section: Introductionmentioning
confidence: 99%